Foreign experts and unsustainable development : transferring Israeli technology to Zambia, Nigeria and Nepal - Schwartz, Moshe; Hare, A. Paul (Alexander Paul), 1923- (Aldershot, Hants, England ; Brookfield, Vt. : Ashgate, 2000)
In the 1950s and 60s, former Asian and African colonies gained independence and became "new states". Examining the three case studies of Nigeria, Nepal and Zambia, this text explores Israel's keenness to forge links with these "new" countries, and its success in assisting them.
Includes bibliographical references (p. 193-202) and index.
oif 17/09/15
Loan
Keywords: Technical assistance, Israeli -- Zambia; Technical assistance, Israeli -- Nepal; Technical assistance, Israeli -- Nigeria